The Values of Islamic Banking as Drivers of Transformation Educational Management: An Islamic Economic Approach and Pedagogical Leadership - Marlina, Reni; Hendriawan, Erry; Irnawati, Riska; Awaliyah, Wiwin; D, Dadang (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Abstract: The transformation of educational management is strategic in addressing contemporary challenges, particularly within Islamic institutions. This study analyzes the integration of Islamic banking values trust, justice, transparency, and social responsibility into educational management and pedagogical leadership, viewed through Islamic economics. Using a qualitative literature review, data were gathered from academic journals, books, and relevant publications, then analyzed via reduction, categorization, and thematic synthesis. Findings indicate that Islamic banking values significantly drive transformation in governance, organizational culture, and human resource development. Furthermore, Islamic economics-based pedagogical leadership bridges the gap between normative vision and operational practice, fostering a participatory, fair, and sustainable environment. However, challenges remain in fully internalizing these values into policies and evaluation mechanisms. The study concludes that integrating Islamic banking principles with pedagogical leadership is a strategic approach for transforming educational management. These findings contribute to the development of Islamic educational management theory and offer practical implications for strengthening value-based institutional governance and leadership.